Interhemispheric Asymmetry in the Seasonal Ionospheric Outflow - N. Nowrouzi; B. M. Walsh (Geophysical Research Letters)
Abstract A comprehensive statistical study is conducted on O+ and H+ outflows obtained from the TEAMS/FAST data during the 23rd solar cycle (1996–2007). The study investigates interhemispheric asymmetry in ionospheric outflows during local summer, winter, and equinox seasons. Data are classified into two distinct periods: the pre‐storm and geomagnetic storm phases. Numerous statistical asymmetries are identified. The findings indicate that the dayside cusp consistently demonstrates more outflow rates of O+ and H+ in the northern hemisphere than southern hemisphere during geomagnetic storms in all seasons as well as during the pre‐storm period in the summer season with the exception of H+ during summer storms. Conversely, the nightside O+ and H+ outflow rates are higher in the southern hemisphere during pre‐storm and storm periods in the summer season. Additionally, the dawnside and duskside outflow rates of O+ and H+ are predominantly stronger in the southern hemisphere.